Unknown God, Known in His Activities Incomprehensibility of God during the Trinitarian Controversy of the 4th Century - Stępień, Tomasz (European Studies in Theology, Philosophy and History of Religions, 2018)
What can man know about God? This question became one of the main problems during the 4th-century Trinitarian controversy, which is the focus of this book. Especially during the second phase of the conflict, the claims of Anomean Eunomius caused an emphatic response of Orthodox writers, mainly Basil of Caesarea and Gregory of Nyssa. Eunomius formulated two ways of theology to show that we can know both the substance (ousia) and activities (energeiai) of God. The Orthodox Fathers demonstrated that we can know only the external activities of God, while the essence is entirely incomprehensible. Therefore the 4th-century discussion on whether the Father and the Son are of the same substance was the turning point in the development of negative theology and shaping the Christian conception of God.